Los responsables de sistemas de información ante el outsourcing: Un análisis empírico y longitudinal - M. R. González Ramírez; J. L. Gascó Gascó; Juan Llopis Taverner (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2008)
Information systems Outsourcing has grown dramatically in recent years. As a result, the professional aspects in the job of the persons in charge of these systems, the CIOs (Chief Information Officers) have changed. As there do not exist many studies about the influence of Outsourcing over the CIO, this study tries to cover this gap. The results of a survey about this issue carried out in Spanish largests firms are shown. A longitudinal analysis is exhibited and an attempt is made to create a business typology, according the way in which outsourcing has influenced the job of the CIOs.
Keywords: 330; information systems outsourcing; CIO; longitudinal study; factor analysis; cluster analysis